Stellar formation and young clusters in NGC 2366 – main properties - Feinstein Baigorri, Carlos (2024)
The characteristics of the young stellar population in the nearby irregular galaxy NGC 2366 were investigated. In particular, we focused our attention on its hierarchical clustering distributions and the properties of the stellar groups. This galaxy exhibits a prominent blue helium-burning star feature in the colour-magnitude diagram, suggesting that it has undergone an extended period of stellar formation. The galaxy was observed in two bands by the Hubble Space Telescope covering almost its complete central and intermediate parts, including all the major stellar formation regions. Available photometric data allowed us to select the blue and young stars and, therefore, study the recent stellar formation. Through the path linkage criterion (PLC), we found 23 young star groups and estimated their fundamental parameters, such as their stellar densities, sizes, and number of members. We also performed a fractal substructure analysis to determine the clustering properties of this population, and we built a stellar density map corresponding to the galactic young population. We found that most of the young stellar groups have stars that have a distribution of locations that is compatible with a fractal dimension.